Tindak Tutur Penolakan Bahasa Jepang oleh Mantan Kenshuusei (Pekerja Magang di Jepang) - Novitasari, Dewi; Aryanto, Bayu (Japanese Research on Linguistics, Literature, and Culture, 2020)
This study is intended to describe the speech act strategy of rejection in Japanese language by former apprentices (kenshuusei). The descriptive qualitative method used in this research is under the approach of interlanguage pragmatic study because the participants are foreign speakers of Japanese. The data were collected using the oral-discourse completion test technique. The findings of this study have shown three types of refusal processes, namely 1) pre-refusal - main refusal - post refusal; 2) pre-refusal - the main refusal; and 3) major refusal - post refusal. In the refusal utterances, there are 2 forms of refusal, namely direct refusal and indirect refusal. The strategies used in refusing are apology strategy, refusal reason strategy, alternative statement strategy, hope statement strategy, future demand strategy, negation form, fukushi, and aizuchi. The refusal strategies mostly used by former apprentices are the excuse strategy for refusal and almost all refusal speeches also use apologies.